Self-concept promote subjective well-being through gratitude and prosocial behavior during early adolescence? a longitudinal study - Jing Li; Yanjiao Li; Yadong Ding (BMC Psychology)
Abstract Whether and how self-concept link subjective well-being (SWB) among early adolescents is an important issue. This study employs longitudinal method to explore the relationship between self-concept and SWB, as well as the mediating effects of gratitude and prosocial behavior on this relationship in early adolescents. A total of 554 early adolescents completed scales at two waves, with a 10-month interval between two measurements. Results showed that, from the perspective of cross-section, self-concept T1 had an indirect effect on SWB T1 through gratitude T1 and prosocial behavior T1. From the longitudinal perspective, self-concept T1 had an indirect predictive effect on SWB T2 through gratitude at T1 and T2, as well as prosocial behavior at T1 and T2. In a word, self-concept positively predicted SWB indirectly in that they positively predicted gratitude and prosocial behavior. These findings help to enrich existing literature and provide a new scientific insight for effectively enhancing early adolescents’ SWB. Implications and limitations were also discussed.